Aberrant Expression of ACO1 in Vasculatures Parallels Progression of Idiopathic Pulmonary Fibrosis - Fukumoto, Jutaro; Lin, Muling; Banday, Mudassir Meraj; Patil, Sahebgowda Sidramagowda; Krishnamurthy, Sudarshan; Breitzig, Mason; Soundararajan, Ramani; Galam, Lakshmi; Narala, Venkata Ramireddy; Johns, Colleen; Patel, Kapilkumar; Dunning, John; et al. (Frontiers in Pharmacology, 2022)
ABSTRACT Rationale: Idiopathic pulmonary fibrosis (IPF) is characterized by mitochondrial dysfunction. However, details about the non-mitochondrial enzymes that sustain the proliferative nature of IPF are unclear. Aconitases are a family of enzymes that sustain metabolism inside and outside mitochondria. It is hypothesized that aconitase 1 (ACO1) plays an important role in the pathogenesis of IPF given that ACO1 represents an important metabolic hub in cytoplasm. Objectives: To determine if ACO1 expression in IPF lungs shows specific patterns that may be important in the pathogenesis of IPF. To determine the similarities and differences about ACO1 expression in IPF, bleomycin-treated, and aging lungs. Methods: ACO1 expression in IPF lungs was characterized and compared to non-IPF controls by western blotting, immunostaining and enzymatic activity assay. ACO1-expressing cell types were identified by multicolor immunostaining. Using similar methods, the expression profiles of ACO1 in IPF lungs versus bleomycin-treated and aged mice were investigated. Measurements and main results: Lower lobes of IPF lungs, unlike non-IPF controls, exhibit significantly high levels of ACO1. Most of the signals colocalize with von Willebrand factor (vWF), a lineage marker for vascular endothelial cells. Bleomycin-treated lungs also show high ACO1 expressions. However, most of the signals colocalize with E-cadherin and/or prosurfactant protein C, representative epithelial cell markers, in remodeled areas. Conclusions: A characteristic ACO1 expression profile observed in IPF vasculatures may be a promising diagnostic target. It also may give clues as to how de novo angiogenesis contributes to the irreversible nature of IPF.